Promising physicochemical technologies for poultry slaughterhouse wastewater treatment: A critical review - Hilares R.T. (2021)
Poultry slaughterhouse wastewater (PSWW) is a serious concern mainly due to the huge generation and associated characteristics of high organic matter and nutrients (N, P) that this contains. Therefore, an understanding development and adaption of an apposite wastewater treatment option focused specifically on PSWW is an absolute need. Recently, innovative physicochemical-based technologies, such as; acid precipitation, electrochemical advanced oxidation, cavitation-based processes and even nanotechnology assisted processes have been reported as prominent alternatives for wastewater treatment. In this article, we performed a systematic literature review and a comprehensive discussion about these technologies, aiming to show them as alternatives for PSWW treatment. Among all discussed technologies, hydrodynamic cavitation (HC) was observed as an interesting possibility that can be implemented in combination with other processes for efficient pollutant degradation. It could be, e.g., associated with nanoparticles, nanocomposites and nanobubbles, which are also an interesting alternative to be associated with membranes, generating turbulence, and mitigating problems as fouling. Finally, the wide knowledge about such treatment technologies can offer a more cost-effective PSWW management, thus, allowing an adequate implementation from technical and economical viewpoints. © 2021 Elsevier Ltd.